1999
DOI: 10.1002/(sici)1099-0690(199906)1999:6<1367::aid-ejoc1367>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

On the Stereochemistry of Tethered Intermediates inp-Methoxybenzyl-Assisted β-Mannosylation

Abstract: We have previously developed a novel method for the stereocontrolled synthesis of β‐manno‐glycoside. Starting from 2‐O‐PMB (p‐methoxybenzyl)‐protected mannosyl donor 1, conversion into the mixed acetal 3 under oxidative conditions followed by the activation of the anomeric position affords β‐manno‐glycoside as a single stereoisomer. Although the utility of this method has been further demonstrated in the synthesis of the core structure of Asn‐linked glycan chains, there remained uncertainty with respect to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…A stereochemical assignment of this intermediate was mentioned by Ito and co-workers. 27) Subsequent IAD was effected by methyl trifluoromethanesulfonate (MeOTf) and 2,6-di-tert-butyl-4-methylpyridine (DTBMP) in dichloromethane to afford the desired b-mannoside 12 in 35% yield and the a-mannoside was not detected. The anomeric hydrogen atom of the mannose unit appeared as a signal at d 4.41 (s, H-1Ј) by the 1 H-NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A stereochemical assignment of this intermediate was mentioned by Ito and co-workers. 27) Subsequent IAD was effected by methyl trifluoromethanesulfonate (MeOTf) and 2,6-di-tert-butyl-4-methylpyridine (DTBMP) in dichloromethane to afford the desired b-mannoside 12 in 35% yield and the a-mannoside was not detected. The anomeric hydrogen atom of the mannose unit appeared as a signal at d 4.41 (s, H-1Ј) by the 1 H-NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Octyl 4, (11) were prepared by literature method. [25][26][27] Octyl 2,3,6-Tri-O-benzyl-b b-D-glucopyranoside (4) To a solution of 3 (1.82 g, 3 mmol) and NaBH 3 CN (1.64 g, 24 mmol) in dry tetrahydrofuran (THF) (10 ml) was added 3A MS, and the mixture was stirred for 2 h at room temperature, then cooled to 0°C. HCl-Et 2 O was added until the solution was acidic (pH paper, gas evolution).…”
Section: Methodsmentioning
confidence: 99%
“…(12,40). Stereochemical and mechanistic insights of this reaction were also attained by modeling and with NMR spectroscopy (41,42). More recently, a 2-O-NAP (NAP: naphthylmethyl)-protected donor was shown to be more efficient, giving a variety of 1,2-cis-glycosides (β-Man, α-Glc, β-Araf ...) in a highly selective manner (43).…”
Section: C-4 Development Of New Reactions For the Synthesis Of Glycomentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27] Tethering proceeded very efficiently using a slight excess of either donor or acceptor (typically 1.1-1.4 equiv relative to the other component) to give mixed acetals, which were either purified by size-exclusion chromatography or used crude in the next step. Activation with MeOTf, DTBMP, 4 Å in DCE or DCM gave the b-mannosides exclusively.…”
Section: Oxidative Tethering: Pmb and Modified Pmb Acetalsmentioning
confidence: 99%
“…Ito and Ogawa showed that in a reverse tethering approach, where the PMB ether is attached to the aglycon (i.e., at the position to be glycosylated) and tethered to a glycosyl fluoride with free OH-2, the mixed acetal can be formed, but as a different diastereomer (i.e., opposite configuration at the new centre) or a mixture of diastereomers (Scheme 9). 21 The origin of the stereoselectivity is obscure, but it seems that the reaction operates under kinetic control. NOE measurements and computational studies were used to deduce the configuration at the newly formed stereogenic centre (from the forward tethering approach shown in Tables 4 and 5), which was assigned as S.…”
Section: Oxidative Tethering: Pmb and Modified Pmb Acetalsmentioning
confidence: 99%